MAP: A mnemonic for mapping BCTs to three routes to behaviour change. Issue 4 (27th July 2020) - Dixon, Diane; Johnston, Marie
Abstract : Objective: Over 90 behaviour change techniques (BCTs) have been specified but there is limited guidance to assist non‐specialist practitioners in the choice of which BCTs to select for use with clients. This paper describes the development of MAP, a theory‐based mnemonic designed to aid practitioners in their use of BCTs. Each BCT is MAPed to one or more of three recognized routes to behaviour change, namely Motivation development, Action control, and Prompted or cued route. Design: A cross‐sectional online discriminant content validity (DCV) questionnaire. Methods: Fourteen judges participated, decided whether each BCT affects behaviour via each of the three routes, and provided a confidence rating for each judgement. Wilcoxon one‐sample tests classified each BCT to a route or combination of routes. Intraclass correlation coefficients (ICC) assessed agreement between judges. Results: Fifty‐eight BCTs were judged to affect behaviour via a single route; 28, 21, and nine BCTs were judged to act via the Motivation, Action, or Prompted routes, respectively. Judges did not agree on a route for 35 BCTs. Overall ICC (0.89) value was high and did not differ between routes. Conclusions: There was good agreement on candidate BCTs for interventions designed to operate through Motivation, Action, or Prompted/Cued psychological processes. MAP is a mnemonic that can be used by non‐specialist practitioners who implement behaviour change with their clients. MAP is not a replacement for sophisticated theory‐based organization of BCTs required for theory testing. While providing practical guidance, further work is necessary to establish effectiveness of BCTs tailored to each route.